Garden City : Supergreen Buildings, Urban Skyscapes and the New Planted Space - Yudina, Anna (London : Thames & Hudson, 2017)
Concrete horizons, urban sprawl, high-density living: never have our cities and their buildings been in greater need of greening. Yet what's required is more than an occasional vertical garden or living roof. Featuring seventy projects from around the world - some built, some ongoing, some from the future - Garden City looks at the increasingly inventive ways in which architects and designers are incorporating nature into the built environment, transforming the city for the benefit of all.
Introduction -- Fusion -- Expansion -- Coexistence -- Performance -- Fusion 2.0.
"With 308 illustrations"--title page.
Keywords: Garden cities; Sustainable architecture